Absence of the kinase S6k1 mimics the effect of chronic endurance exercise on glucose tolerance and muscle oxidative stress - C. Binsch; T. Jelenik; A. Pfitzer; M. Dille; S. Müller-Lühlhoff; S. Hartwig; S. Karpinski; S. Lehr; D.G. Kabra; A. Chadt; M. Roden; H. Al-Hasani; et al. (Elsevier, 2017)
Objective: Ribosomal protein S6 Kinase-1 (S6K1) has been linked to resistance exercise-mediated improvements in glycemia. We hypothesized that S6K1 may also play a role in regulating glycemic control in response to endurance exercise training. Methods: S6k1-knockout (S6K1KO) and WT mice on a 60 cal% high-fat diet were trained for 4 weeks on treadmills, metabolically phenotyped, and compared to sedentary controls. Results: WT mice showed improved glucose tolerance after training. In contrast, S6K1KO mice displayed equally high glucose tolerance already in the sedentary state with no further improvement after training. Similarly, training decreased mitochondrial ROS production in skeletal muscle of WT mice, whereas ROS levels were already low in the sedentary S6K1KO mice with no further decrease after training. Nevertheless, trained S6K1KO mice displayed an increased running capacity compared to trained WT mice, as well as substantially reduced triglyceride contents in liver and skeletal muscle. The improvements in glucose handling and running endurance in S6K1KO mice were associated with markedly increased ketogenesis and a higher respiratory exchange ratio. Conclusions: In high-fat fed mice, loss of S6K1 mimics endurance exercise training by reducing mitochondrial ROS production and upregulating oxidative utilization of ketone bodies. Pharmacological targeting of S6K1 may improve the outcome of exercise-based interventions in obesity and diabetes.